Nephroprotective Potentials of Ethanol Leaf Extract of Balakat Tree (Ziziphus Talanai) (Blanco) Merrill. Against Gentamicin- Induced Nephrotoxicity in Male Icr Mice (Mus Musculus L.) - Oliver Ysais Galang; Angelico G. Reyes; Lourdes Fatima S. David; Renato A. Dela Peña, Jr.; Renz Joshua D. De Vera (Journal of Healthcare and Biomedical Science, 2024)
Renal dysfunction can be caused by antibiotic drugs like Gentamicin, which can induce lipid peroxidation, increase free radical synthesis, and decrease antioxidant activity, leading to kidney failure. In the antiques, Philippines, an endemic species of Ziziphus, Ziziphus talanai (Balakat tree), is used as a traditional medicine to treat kidney problems. Phytochemical screening of the ethanol leaf extract of the Balakat tree revealed its potential as a nephroprotective agent. Twelve 6- to 8-week-old male ICR mice were divided into four groups, and treatments were administered for 18 days. Gentamicin was administered intraperitoneally, whereas water, leaf extract, and garlic supplement were administered via oral gavage. The ethanolic leaf extract of the Balakat tree exhibited little potential as a nephroprotective agent at the single dosage used (0.3ml/20g bw), and further studies involving higher doses are recommended. These findings suggest that the ethanolic leaf extract of the balakat tree has potential as a nephroprotective agent. Further studies with higher doses are recommended.